Penegakan Kepastian Hukum Dalam Unsur Tindak Pidana Penganiayaan Berencana Pada Putusan Pengadilan Negeri MARISA 72/PID.B/2019/PN.MAR - Arif Al Jibran, Farel; Adhari, Ade (Universitas Ekasakti, 2024)
Enforcing legal certainty in criminal acts of serious abuse is an important aspect of a just justice system. This study analyzes the application of the elements